Metallosis in a total knee arthroplasty - Vivegananthan, Bhairavi (BMJ Publishing Group, 2014)
A 70-year-old woman presented with right knee pain and a ‘grinding’ sensation 6 months after a total knee replacement for osteoarthritis. Clinical examination revealed a valgus deformity, patellofemoral crepitus and a reduced knee flexion. Radiographs revealed distinctive findings including the ‘bubble sign’, ‘cloud sign’ and the ‘metal line sign’, which are diagnostic of metallosis.Metallosis is an uncommon complication of total joint replacements, where bone and periprosthetic soft tissues are infiltrated by metallic debris from wearing of the prostheses. This usually occurs in high-wear joints such as hips and knees. Treatment for patients diagnosed with metallosis is synovectomy and a revision surgery. Our patient underwent revision surgery 5 years after her initial surgery.